Quality education service: put your feet in their shoes. Issue 11 (18th September 2016) - Cheng, Ching-Chan; Tsai, Ming-Chun; Lin, Chien-Lin
Abstract : This study aims to integrate importance-performance and gap analysis (IPGA), decision-making trial and evaluation laboratory (DEMATEL), and quality function deployment (QFD) to develop a three-tiered service-quality-improvement model in order to identify critical educational-service-quality deficiencies in hospitality, tourism, and leisure undergraduate programmes and thereafter to formulate applicable service-improvement strategies. Seven hundred and eighty-six valid questionnaires were returned. The IPGA analysis showed 12 service-quality attributes were in the area of 'Concentrate here'. Out of the 12 attributes, four main cause attributes were found with the DEMATEL analysis. Furthermore, six service-improvement strategies were developed based on experts' in-depth interviews and QFD analysis. The effects of these improvement strategies were fully discussed in the context.